Penal Policy Analysis of The Formulation of Customary Law in The 2023 KUHP - Umi Rozah; Aldi Yudistira (Indonesian Journal of Criminal Law Studies, 2025)
An interesting issue in the 2023 Criminal Code is the accommodation of living law with a meaning limited to Customary Law as formulated in Article 2, Paragraphs (1), (2), and (3). This research aims to analyze it from the perspective of penal policies regarding the formulation of Living Law only as Customary Law in Article 2, Paragraphs (1), (2), and (3) of the 2023 Criminal Code. This research uses a normative or doctrinal juridical approach, with data sources from library materials in the form of statutory regulations and literature related to research.   This research raises problems: 1). How does analysis of the penal policy of the formulation of living law in Article 2 Paragraph (1) of the 2023 Criminal Code (KUHP)? 2). What is a reformulation of Article 2 Paragraph (1), Paragraph (2), and Paragraph (3) of the 2023 KUHP from a penal policy perspective?  The results of the research are as follows: There is invalidity in the formulation of the meaning of living law as only Customary Law as the living law is wider than Customary Law. It covers all customs in society, such as business affairs and religious life. Analysis from a penal policy perspective can’t be adjusted if the meaning of living law is only determined by Customary Law. There are many fallacies in the formulation of Article 2, Paragraphs (1), (2), and (3) of the 2023 KUHP, so reformulation is needed. Reformulation of Article (2) Paragraphs (1), (2), and (3) should be changed to interpret the living law not only as Customary Law, which will be formulated in Regional Regulation. Article (2) Paragraphs (1), (2), and (3) are just needed as the recognition rules to enforce Customary Law; in other words, formulation of the living law only as an umbrella rule to enforce Customary Law.